Immigration and Higher Education: Competition for Talent - Kent, Daniel (International Higher Education, 2022)
Countries take a variety of approaches to their international students who graduate locally and seek to stay. While some offer significant time horizons to search for and acquire a job, or eliminate needed sponsorship altogether, not all are as generous. Yet in both instances, local graduates acquire experience that gives them inherent advantages, should they desire to stay after completing their studies.